Analisis Pemberian ASI Ekskluisf pada Ibu Pekerja di Wilayah Kerja Puskesmas Simpang Babat Tahun 2026 - Gita Listawaty; Arie Wahyudi; Lilis Suryani (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Exclusive breastfeeding is an important intervention to improve infant health status, growth, and development. However, the coverage of exclusive breastfeeding among working mothers remains suboptimal. This study aimed to analyze factors associated with exclusive breastfeeding among working mothers in the Simpang Babat Public Health Center working area, Penukal Abab Lematang Ilir (PALI) Regency. This study employed an analytic observational design with a cross-sectional approach conducted from February to June 2026. The study population consisted of 133 working mothers with infants aged 0–12 months, and a sample of 100 respondents was selected using proportional random sampling. Data were collected using a structured questionnaire and analyzed using the chi-square test and multiple logistic regression. The results showed that 55% of respondents did not practice exclusive breastfeeding. Bivariate analysis revealed that family economic status (p=0.001), maternal psychological condition (p=0.004), husband's support (p<0.001), workplace facilities support (p<0.001), and maternal knowledge (p=0.028) were significantly associated with exclusive breastfeeding. Multivariate analysis indicated that family economic status was the most dominant factor associated with exclusive breastfeeding (OR=15.866; 95% CI=3.618–69.582). In conclusion, exclusive breastfeeding among working mothers was associated with family economic status, maternal psychological condition, husband's support, workplace facilities support, and maternal knowledge. These findings highlight the need to strengthen breastfeeding education, increase husband involvement, and provide adequate lactation facilities in the workplace to support exclusive breastfeeding among working mothers.